A comprehensive presentation of Iran's human resources for health information systems: A mixed-method case study. Issue 3 (September 2022) - Zhila, Najafpour; Mohammad, Arab; Kamran, Shayanfard; Masoumeh, Najafi Gharehbelagh; Madineh, Kouhzar
Highlights: HRH information systems have not fully covered the HRH data in all parts of health sectors, particularly the private sector. Using the HRH data is not a routine procedure for strategic planning. The HRHISs has a multitude of problems like unclear organizational structure and governance, lack of standards among HRH measurement tools, weak top-down monitoring mechanism and so on. A functional HRHIS requires good governance, integrating processes in a collaborative mechanism between different health service institutes, national planning for data integrity and accuracy to link HRH data to broader health information. Abstract: Objectives: This study is designed to evaluate the characteristics of the Human Resources for Health Information Systems (HRHISs ) of Iran. It also explores the challenges of HRHISs that need to be addressed to plan a national health workforce strategy. Methods: This mixed-method study was carried out through observational research, and semi-structured interviews with key informants in health policy, information technology and HRH management. It was conducted over two months from May to July 2019. The WHO-HRHIS assessment tool was used during the observational phase. We purposively selected representatives from different organizations and departments involved in managing the HRHIS. In the qualitative phase, purposeful and snowball sampling methods were used, and 20 interviews were conducted that each lasted minimum of 45 minutes. A content analysis was used to discuss findings. Results: Human Resources (HR) departments are fully equipped with information communication technology (ICT). There were 30 different HRH databases with varying HRH data elements ranging from 10 to 115 HRH data elements. Sixty-three percent of the databases were directly captured data online and daily (78%). Most organizations had no feedback mechanism for cross-checking the HRH data; only 28 % of the databases were accurate and trustworthy. Data analysis was not a regular input in the decision-making process. Data reporting and information dissemination were not provided regularly. We categorized HRHISs weaknesses into the following themes: managerial, technical, infrastructural, and systemic barriers. The categories included unintegrated governance, miscommunication between the MoHME and other organizations, organizational factors, inaccuracy in HRH data, wide disparities of HRH information in databases, infrastructural weaknesses, inadequate competent staff, and non-use of research evidence in decision making. Conclusions: The overall HRHIS assessment demonstrated an unintegrated computerized system with various data elements generated through multiple databases in different sectors. It has not fully covered the HRH data in all parts of health sectors, particularly the private sector. This study illustrates that the current HRIS used in the country have several major challenges. We suggest planning on the identified barriers of HRHISs so that the gaps are better tackled to implement the "Global Strategy on Human Resources for Health: Workforce 2030".